2020
DOI: 10.1016/j.medcli.2020.04.012
|View full text |Cite
|
Sign up to set email alerts
|

COVID-19 grave con inicio como neumonía bilateral, ictus isquémico e infarto de miocardio

Abstract: Since January 2020 Elsevier has created a COVID-19 resource centre with free information in English and Mandarin on the novel coronavirus COVID-19. The COVID-19 resource centre is hosted on Elsevier Connect, the company's public news and information website. Elsevier hereby grants permission to make all its COVID-19-related research that is available on the COVID-19 resource centre -including this research content -immediately available in PubMed Central and other publicly funded repositories, such as the WHO … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
8
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(9 citation statements)
references
References 0 publications
1
8
0
Order By: Relevance
“…Comparing these patients with our stroke registry of 8,929 AIS patients (GNSIS, Geisinger NeuroScience Ischemic Stroke database) indicated a higher prevalence of patients with no known risk factor (22.0% in this study versus 11.5% in GNSIS, p<0.001). We also observed that the patients in this study were younger (60.0±18.0 years versus 62.9±17.6 years, p=0.004) and had more severe strokes (NIHSS of 8 [4][5][6][7][8][9][10][11][12][13][14][15][16][17][18][19][20][21][22] Among the AIS patients, 13.6% of patients received intravenous thrombolysis, while 7.4% underwent mechanical thrombectomy. These rates are similar to the multinational study on 174 AIS SARS-CoV-2 infected patients (12.7% thrombolysis, 6.9% thrombolysis, and thrombectomy, and 5.2% mechanical thrombectomy).…”
Section: Discussionsupporting
confidence: 58%
See 2 more Smart Citations
“…Comparing these patients with our stroke registry of 8,929 AIS patients (GNSIS, Geisinger NeuroScience Ischemic Stroke database) indicated a higher prevalence of patients with no known risk factor (22.0% in this study versus 11.5% in GNSIS, p<0.001). We also observed that the patients in this study were younger (60.0±18.0 years versus 62.9±17.6 years, p=0.004) and had more severe strokes (NIHSS of 8 [4][5][6][7][8][9][10][11][12][13][14][15][16][17][18][19][20][21][22] Among the AIS patients, 13.6% of patients received intravenous thrombolysis, while 7.4% underwent mechanical thrombectomy. These rates are similar to the multinational study on 174 AIS SARS-CoV-2 infected patients (12.7% thrombolysis, 6.9% thrombolysis, and thrombectomy, and 5.2% mechanical thrombectomy).…”
Section: Discussionsupporting
confidence: 58%
“…[5,78,79,83] In addition, less severe stroke symptoms, mostly in critically ill patients or overwhelmed health centers, were more likely to be under-diagnosed. We observed a lower median NIHSS score in countries with middle to high-health expenditure-8 [3][4][5][6][7][8][9][10][11][12][13][14][15][16][17] versus 11 [5][6][7][8][9][10][11][12][13][14][15][16][17] in countries with lower health expenditure. The regional difference in the severity of stroke in our study-NIHSS of 12 [6][7][8][9][10][11][12][13][14][15][16][17] in the Middle East, versus 7[0-16] in America and 8 [4][5][6][7]…”
Section: Discussionmentioning
confidence: 55%
See 1 more Smart Citation
“…Despite several reports of special features and probable underlying coagulopathy in AIS with prior SARS-CoV-2 infection [ 2 , 4 , 6 , 7 , 8 , 9 , 10 ], similar reports are lacking in the literature regarding acute coronary syndrome and cardiovascular thromboembolic events. The majority of adverse outcomes among patients with stroke [ 39 , 40 ] or acute coronary syndrome [ 11 , 12 , 13 , 14 , 15 ] were related to the declining trend in seeking urgent care, hospitalization, and receiving guideline indicated measures.…”
Section: Discussionmentioning
confidence: 99%
“…Some reports have highlighted strokes in critically ill and older patients with a higher number of comorbidities, while others have suggested a higher risk in younger and healthy individuals [ 1 , 2 , 3 , 4 , 5 ]. Studies have suggested that stroke patients with SARS-CoV-2 present with multiple cerebral infarcts [ 2 , 4 , 6 ], systemic coagulopathies [ 7 ], uncommon thrombotic events such as aortic [ 8 ] or common carotid artery thrombosis [ 9 ], and simultaneous arterial and venous thrombus formation [ 10 ].…”
Section: Introductionmentioning
confidence: 99%